China as the next champion of globalisation? - Wu, Friedrich (2017)
As the US under Donald Trump and European powers like Britain and France turn their backs on globalisation, could or would China step in to be the next champion of globalisation? As Beijing attempts to demonstrate leadership and garner global trust through initiatives like AIIB and OBOR, a litmus test awaits President Xi Jinping and his "pro-globalisation" team.